Stakeholder viewpoints on facilitation of cross-border cooperation. Issue 4 (3rd April 2022) - Borges, João Augusto Rossi; Neuberger, Sabine; Saatkamp, Helmut; Oude Lansink, Alfons; Darr, Dietrich
ABSTRACT: The European Union fosters cooperation in cross-border regions through the European Cohesion Policy (ECP). The implementation of ECP instruments requires a participatory approach, in which stakeholders' views are acknowledged. However, the multiple of views among and between stakeholders of cross-border initiatives complicate their involvement in a participatory approach. A prerequisite for a meaningful involvement of all stakeholders is an in-depth understanding of their viewpoints on what facilitates cross-border cooperation. However, to date, these viewpoints are poorly understood. This study aims to identify and analyse stakeholders' viewpoints on the facilitation of cross-border cooperation. The viewpoints of a sample of entrepreneurs, members of education institutes, and members from local institutions (policymakers and industry representatives) in the Dutch-German cross-border region Rhine-Waal were collected via Q methodology and complemented through interviews. Four viewpoints emerged: cooperation through pro-active engagement, cooperation through targeted policies, cooperation through an aligned institutional setup, and cooperation through socio-cultural proximity. Results can inform policy-making aimed to increase stakeholder involvement in participatory approaches in cross-border regions.